Effect of Milling Methods on Flow Properties of Whole Pearl Millet Flours - Del C., Berta G. (Zamorano: Escuela Agrícola Panamericana, 2024)
In recent years, there has been interest in the use of pearl millet as flour for human consumption due to its nutritional quality and gluten-free nature. However, studies on the particle level that relates to its processing and handling are limited. The effect of different milling methods (roller mill, pin mill, and hammer mill) on the particle size distribution and flowability of pearl millet flour was evaluated. The physicochemical properties (moisture, water activity, ash content, and damaged starch), particle size distribution, and shape characteristics were investigated and correlated with flow properties. Flowability was measured in terms of bulk, dynamic, and friction flow properties using the FT4 powder rheometer. Pin mill and hammer mill exhibited the highest bulk density (537.83 and 555.26 kg/m³) and tapped density (641.71 and 670.13 kg/m³). No differences were found for true density, compressibility index, and Hausner ratio among the three different milling methods. However, when the flour was subjected to an applied normal stress, the compressibility percentage was significantly higher for pin mill and hammer mill. Roller mill had the best permeability at different applied normal stresses and lower energy consumption during the stability test at different blade velocities. Pin mill and hammer mill flours are more susceptible to different air velocities, presenting the best aerated energy (573.33mJ and 544.34 mJ), aeration ratio (2.25 and 2.34), and normalized aeration sensitivity (0.070 and 0.068). The three milling methods showed the same behavior for wall friction angle at different applied pressures. The results of this study showed the importance of milling methods to achieve better flow behavior of pearl millet flour during processing and storage.